LPCAT1 enhances the invasion and migration in gastric cancer: Based on computational biology methods and in vitro experiments - Zu‐Xuan Chen; Liang Liang; He‐Qing Huang; Jian‐Di Li; Rong‐Quan He; Zhi‐Guang Huang; Rui Song; Gang Chen; Jian‐Jun Li; Zheng‐Wen Cai; Jie‐An Huang (Cancer Medicine, 2023)
Abstract Background and Aim The biological functions and clinical implications of lysophosphatidylcholine acyltransferase 1 (LPCAT1) remain unclarified in gastric cancer (GC). The aim of the current study was to explore the possible clinicopathological significance of LPCAT1 and its perspective mechanism in GC tissues. Materials and Methods The protein expression and mRNA levels of LPCAT1 were detected from in‐house immunohistochemistry and public high‐throughput RNA arrays and RNA sequencing. To have a comprehensive understanding of the clinical value of LPCAT1 in GC, all enrolled data were integrated to calculate the expression difference and standard mean difference (SMD). The biological mechanism of LPCAT1 in GC was confirmed by computational biology and in vitro experiments. Migration and invasion assays were also conducted to confirm the effect of LPCAT1 in GC. Results Both protein and mRNA expression levels of LPCAT1 in GC were remarkably higher than those in noncancerous controls. Comprehensively, the SMD of LPCAT1 mRNA was 1.11 (95% CI = 0.86–1.36) in GC, and the summarized AUC was 0.85 based on 15 datasets containing 1727 cases of GC and 940 cases of non‐GC controls. Moreover, LPCAT1 could accelerate the invasion and migration of GC by boosting the neutrophil degranulation pathway and disturbing the immune microenvironment. Conclusion An increased level of LPCAT1 may promote the progression of GC.